Perception of agriculture students about virtual reality in learning: Empirical evidence from students' exposure to VR module on downy mildew of grapes - Chusmitha, SGP; Balasubramaniam, P; Anandaraja, N; Keisar , L D; SHIVAKUMAR, K M (Plant Science Today, 2025)
The study examines the perception of agricultural students at Tamil Nadu Agricultural University towards a Virtual Reality (VR) module on Downy Mildew of Grapes. The aim of the study is to assess agriculture students' perception and learning outcomes using a VR module on downy mildew of grapes. The research design was ex post facto. Students who have undertaken the VR module-downy mildew of grapes session were taken purposefully, because large number of students attended this VR module. In this research, 150 students were selected by simple random sampling method. The information was gathered from students by both telephonic and direct interviews using well-organised questionnaire. The research findings showed that students had a favourable and positive opinion towards the VR module. Also, it insists that previous experience among the students in VR and confidence in the students improve their understanding and opinion towards VR module, whereas prior experience in VR and self-confidence had significant positive association with students' perception towards VR module. This result also contains some challenges faced by the students during VR classes, like discomfort, fear, less knowledge and technical issues. It also recommended some suggestions to improve the VR classes. This concluded that the students felt VR module was effective and efficient for their education and VR helped them in order to improve their knowledge, understanding and skills.